National security : emerging dimensions and threats - Gandhi, Navniit ([S.l.] : Pentagon Press, 2010)
Insecurity is not just all pervasive but is reiterating its alarming overtones more forcefully than during the cold war era. There are now threats very different from a military attack on a nation's territory. The concept of National Security hence needs to be redefined. The gamut of its perceptions has undergone a paradigm shift. The context against which the policy makers seek to establish national security is undergoing tumultuous changes. While not downplaying the relevance of strategic means of maintaining national security, this book explores the emerging non-strategic threats to national security, with the obvious grave consequences on human security. This book attempts to address several questions: Can the concepts of National Security and Human Security be reconciled meaningfully? Can their approaches and objectives be inter-twined so that we can live a fuller life? Can the nations and citizenry-both feel equally secure at the same time?
Keywords: National security; Security, International